Toward a Generalized Accelerator for Genome Sequence Analysis. - Turakhia, Yatish (Communications of the ACM, 2025)
This article details the current state of hardware accelerators for dynamic programming (DP) algorithms for genomics applications with a look at Gu et al.’s work in “GenDP: A Framework of Dynamic Programming Acceleration for Genome Sequencing Analysis” which aims to improve adaptability of these accelerators. This article touches upon Gu et al’s summary of the three limited structural variations in DP kernels as well as details the two major components of GenDP- a programmable DP accelerator and a graph-partitioning algorithm.